2017
DOI: 10.1159/000477902
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Brain Network Hubs in Subtype-Specific Parkinson's Disease

Abstract: Background/Aims: The topological organization of brain functional networks is impaired in Parkinson's disease (PD). However, the altered patterns of functional network hubs in different subtypes of PD are not completely understood. Methods: 3T resting-state functional MRI and voxel-based graph-theory analysis were employed to systematically investigate the intrinsic functional connectivity patterns of whole-brain networks. We enrolled 31 patients with PD (12 tremor dominant [TD] and 19 with postural instabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…Similar FC changes have already been reported in literature ( 11 , 52 ). Interestingly, the decreased connectivity within the primary and lateral VNs was accompanied by a significant CBF reduction.…”
Section: Discussionsupporting
confidence: 91%
“…Similar FC changes have already been reported in literature ( 11 , 52 ). Interestingly, the decreased connectivity within the primary and lateral VNs was accompanied by a significant CBF reduction.…”
Section: Discussionsupporting
confidence: 91%
“…These internetwork differences included somatomotor to cortical sensory and association systems and subcortical systems, like the cerebellum and thalamus. Interestingly, lower internetwork FC of the motor system weakly mirrored that found in other sensory systems (visual, auditory, seen also in (Olde Dubbelink et al 2014;Canu et al 2015;Guimaraes et al 2016;Ma et al 2017;Peraza et al 2017)). Reduced internetwork FC between somatomotor and sensory networks in PD may relate to reports of impaired sensory processing and sensorimotor integration (Abbruzzese and Berardelli 2003;Patel et al 2014;Richards et al 1993), as further suggested by the relationship between visual-cerebellar FC and visuospatial performance reported here.…”
Section: Pd Impacts Specific Cortical and Subcortical Network And Ementioning
confidence: 61%
“…The large, prominent, intranetwork and internetwork disruptions of the cerebellar and thalamic systems are particularly interesting. Although known to have central roles in motor function as well as important processing and gating roles for many other cortical networks (Alexander et al 1990;Middleton and Strick 2000;Saalmann and Kastner 2011;Buckner 2013;Hwang et al 2017), few prior studies comprehensively included these regions in studies of connectome-wide disruption in PD (although for cerebellum see (Onu et al 2015;Guimaraes et al 2016;Ma et al 2017) and for thalamus see (Baggio et al 2014;Gorges et al 2015;Vervoort et al 2016)). Our findings indicate that the cerebellum and thalamus may be key sites of dysfunction in PD.…”
Section: Pd Impacts Specific Cortical and Subcortical Network And Ementioning
confidence: 99%
“…superior and inferior longitudinal fasciculus, corpus callosum, pedunculopontine nucleus and corticospinal tract) and functional networks that include many of these regions (e.g., fronto-parietal and default mode networks). PD-PIGD relative to PD-TD is also associated with more gray matter atrophy [171], white matter integrity [232] and altered functional connectivity [118,230,236], yet in a more restricted set of brain regions and tracts, including the amygdala, globus pallidus, corpus callosum, superior longitudinal fasciculus, and functional connectivity between the substantia nigra and putamen, and the caudate and putamen.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%